Prevention of adoptively transferred diabetes in nonobese diabetic mice with IL-10-transduced islet-specific Th1 lymphocytes. A gene therapy model for autoimmune diabetes. - Moritani, M (1996)
Four pancreatic islet-specific CD4+ helper T (Th) 1 (Th1) clones and two Th1 clones transduced with an SRalpha promoter-linked murine IL-10 (mIL-10) cDNA of 2.0-6.0 x 10(6) cells were adoptively transferred to nonobese diabetic (NOD) mice at age 8 d. Cyclophosphamide (CY) was administered at age 37 d (plus CY), and the incidence of diabetes and the histological grade of insulitis were examined at age 47 d. After the adoptive transfer of IL-10-transduced Th1 cells, polymerase chain reaction (PCR) and reverse-transcription (RT)-PCR detected the neo gene and the retrovirus vector-mediated IL-10 mRNA in situ in recipient islets, respectively. RT-PCR detected the decrease of IFN-gamma mRNA relative to IL-10 mRNA in IL-10-transduced Th1 clones in vitro and also in recipient islets. All four wild type Th1 clones plus CY induced the insulitis grade of 2.75 and diabetes in 66% of recipient NOD mice. IL-10-transduced two Th1 clones plus CY induced periinsulitis with the grade of 1.43 and diabetes in 8.0%. The 1:1 mixture of wild type Th1 cells and IL-10-transduced Th1 cells plus CY induced periinsulitis with the grade of 1.85 and diabetes in 20%. The suppression of diabetes through decreasing IFN-gamma mRNA by the tissue-specific delivery of IL-10 to pancreatic islets with IL-10-transduced Th1 cells affords us the starting basis to develop the gene therapy for autoimmune diabetes.